Industrial Archaeology
XIII, 321 p.
Keywords: The essays in this book are adapted from papers presented at the 24th Annual Conference of the Theoretical Archaeology Group, held at the University of Manchester, in December 2002. The conference session "An Industrial Revolution? Future Directions for Industrial Archaeology," was jointly devised by the editors, and sponsored by English Heritage, with the intention of gathering together leading industrial and historical archaeologists from around the world. However, just as Manchester is being transformed by regeneration, shaking off many of the negative connotations associated with factory-based industrial production, and remaking itself as a 21st century city, then so too, is the archaeological study of industrialisation being transformed. Over the past decade, industrial archaeology has emerged as a theoretically driven subfield. Research has begun to meaningfully engage with such weighty issues as globalisation; post/modernity; power; innovation and invention; slavery and captivity; class, ethnic, and gender identities; social relations of technology and labour; and the spread and diversification of western capitalism. With contributions from an international group of authors, this volume highlights the current thought in industrial archaeology, as well as explores future theoretical and methodological directions. Together, these chapters further the process of meaningful engagement with such weighty issues as globalization; post/modernity; power; production and consumption; innovation and invention; class, ethnic, and gender identities; social relations of technology and labour; and the spread and diversification of western capitalism. Industrial Archaeology: Future Directions will be of interest to historical and urban archaeologists, architectural historians, preservation agencies, archaeological consulting organizations, cultural resource managers, and students of these disciplines.